Experimental Approach to Evaluate Effectiveness of Vortex Generators on Francis Turbine Runner - Atmaram Kayastha; Hari Prasad Neopane; Ole Gunnar Dahlhaug (Energies, 2025)
The global need for balance between energy generated from intermittent renewable sources and the actual demand has introduced severe operational challenges on hydropower, a steady energy source in the current context. Although it has some flexibility in operation by varying flow, head, and speed, the entirety of its operational range must be optimized to be more effective. The non-optimal conditions caused by these operational changes result in flow separation on runner blades that results in low efficiency and can be mitigated with the use of vortex generators. The vortex generators can be designed with the empirical method based on the boundary layer height, and the estimated boundary layer height for the Francis turbine runner blade in this study is 2.5 mm. The selected height of the counter-rotating rectangular vortex generators is 5 mm, and two pairs are attached close to the leading edge of the runner blade on the pressure side. The experimental analysis of the runner is conducted at all operating ranges, and efficiency is compared with the reference case. The reliable increment in efficiency obtained is 0.40% ± 0.22%, measured at a GV opening of 13 degrees (full load) and a reference speed of (333 rpm). Similarly, at the same GV opening, the increment in efficiency is obtained at a high speed (408 rpm) with a value of 1.20% ± 0.40%. However, the efficiency increment at part load and the BEP is not as significant since the values lie within the uncertainty band. Thus, these simple passive devices can be employed, and the streamwise vortices generated can be utilized to reduce the impact of flow separation on the Francis runner blades.